2003
DOI: 10.1038/sj.npp.1300213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2D6 Genotypes on the Metabolism of Haloperidol in a Japanese Psychiatric Population

Abstract: We investigated the effect of CYP2D6 genotypes on plasma levels of haloperidol (HAL) and reduced haloperidol (RHAL) in 88 Japanese schizophrenic inpatients being treated with HAL. Some subjects carrying CYP2D6*5 allele (CYP2D6*1/CYP2D6*5, CYP2D6*5/ CYP2D6*10) showed extremely high concentrations of both HAL and RHAL, and the groups with CYP2D6*5 allele seemed to have higher plasma concentrations of HAL (1.14 7 0.69 ng/ml/mg) and RHAL (1.10 7 1.05 ng/ml/mg) than the other groups. Among those without CYP2D6*5 al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…However, Table 4 and Figure 4 showed that subjects with the à 1/ à 10 genotype exhibited a trend toward higher AUC values after the administration of aripiprazole. The à 10 allele, which induces reduction of enzyme affinity for the substrate, has been associated with the high plasma levels and AUC values after the administration of several psychoactive drugs, including haloperidol, nortriptyline, paroxetine and aripiprazole (Yoon et al, 2000;Dalen et al, 2003;Someya et al, 2003;Kubo et al, 2005). Our findings are in accordance with the previous studies, except that subjects with the à 10/ à 10 genotype exhibited lower AUC values than did the subjects with the à 1/ à 10 genotypes (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…However, Table 4 and Figure 4 showed that subjects with the à 1/ à 10 genotype exhibited a trend toward higher AUC values after the administration of aripiprazole. The à 10 allele, which induces reduction of enzyme affinity for the substrate, has been associated with the high plasma levels and AUC values after the administration of several psychoactive drugs, including haloperidol, nortriptyline, paroxetine and aripiprazole (Yoon et al, 2000;Dalen et al, 2003;Someya et al, 2003;Kubo et al, 2005). Our findings are in accordance with the previous studies, except that subjects with the à 10/ à 10 genotype exhibited lower AUC values than did the subjects with the à 1/ à 10 genotypes (Figure 4).…”
Section: Discussionsupporting
confidence: 91%
“…In the former study, the patients were divided into three genotype groups by the number of CYP2D6 mutated alleles: *1/*1, *1/*5 or *1/*10, and *5/*10 or *10/*10, whereas, in this study, the patients were divided into two genotype groups by the degree of enzyme activity: *1/*1 or *1/*10 and *10/*10, *1/*5 or *5/*10. We previously reported that one *5 allele had a greater impact on the metabolism of haloperidol, a substrate of CYP2D6, than one *10 allele (Someya et al, 2003). Since *1/*10 has only one mutation causing decreased enzyme activity, it was supposed that the enzyme activity of *1/*10 was almost equal to that of the *1/*1 genotype in this study.…”
Section: Discussionmentioning
confidence: 61%
“…A recent study investigated the effect of CYP2D6 genotypes on the plasma level of HAL and RHAL in 88 Japanese schizophrenic patients. They found that patients carrying the CYP2D6*5 allele seemed to have a higher plasma level of both HAL and RHAL regardless of carrying the CYP2D6*10 allele or not [29]. Therefore, other genetic analyses for the association between the CYP2D6 gene and TD in the Chinese ethnic subjects deserve attention before drawing any conclusion regarding the role of the CYP2D6 gene on the susceptibility to TD.…”
Section: Discussionmentioning
confidence: 99%